Detection of SNPs in the BMP6 Gene and Their Association with Carcass and Bone Traits in Chicken - Cui,C (2017)
ABSTRACT BMP6, a member of the subfamilies of the morphogenetic proteins (BMPs), plays a crucial role in osteogenic and chondrocyte differentiation in vitro and stimulates chondrogenesis, making chondrocytes differen-tiate on their terminal stage. The objective of this study is to explore the relationship between polymorphism of BMP6 gene and slaughter traits in chicken respectively. We screened the exonic and intronic regions of BMP6 gene by DNA pool construction and amplified DNA fragment by PCR, and finally, we got nine SNPs. Association analysis revealed that BMP6 had no significant association among all slaughter traits in Yellow bantam chicken. However, BMP6 had a significant difference with femur weight, tibia weight, femur length (p<0.05), and was extremely significant with tibia length (p<0.01) in Avian chicken. Moreover, femur perimeter also had significant correlation with BMP6 in Avian chicken. These results provide useful information for further investigation on the function of chicken BMP6 gene.